PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM TINDAK PIDANA KORUPSI (STUDI PUTUSAN PENGADILAN TINDAK PIDANA KORUPSI PADA PENGADILAN NEGERI KELAS I A BENGKULU NO.64/PID.SUS/TPK/2016/PN.BGL) - Frendra AH AH; Alvi Syahrin; Mahmud Mulyadi; Muhammad Ekaputra (Universitas Sumatera Utara, 2018)
ABSTRACT Criminal liability for corporations as provided for in the draft KUHP factors examined is the concept of corporate liability mechanization and itself. Within the scope of criminal liability issues will put forward the question of the corporation as the subject or the maker or the perpetrator of a criminal offence. Formulation of the problem in this research is how corporate setting as a subject of law in the criminal offence of corruption, how does corporate criminal liability in criminal acts of corruption by UU No. 31 Tahun 1999 Jo. UU No.20 Tahun 2001 about the changes to the UU No. 31 Tahun 1999 about the eradication of criminal acts of corruption, and how the criminal liability of corporations in the criminal offence of corruption in ruling No. 64/Pid. Sus/TPK/2016/PN. Bgl. Research purposes ais to know how corporate setting as a subject of law in the criminal offence of corruption, to know how does corporate criminal liability in criminal acts of corruption by UU No. 31 Tahun 1999 Jo. UU No.20 Tahun 2001 about the changes to the UU No. 31 Tahun 1999 about the eradication of criminal acts of corruption, and to know how the criminal liability of corporations in the criminal offence of corruption in ruling No. 64/Pid. Sus/TPK/2016/PN. Bgl. The research is the study of normative descriptive research analytical by nature. The data used the data of primary and secondary legal materials that consist of primary, secondary, and tertiary. Data collection tools and techniques performed with the study of librarianship and study the field by doing the interview. The data analysis done with the method of qualitative analysis. Keywords: accountability, corruption, criminal corporations.